NAVIGATING EMPLOYEEâS ROLE AS INFLUENCERS IN SOCIAL MEDIA: MEASURING EMPLOYEE-BASED BRAND EQUITY USING MIXED METHODS SEQUENTIAL EXPLANATORY MODEL - Bagaskara Reza P, Muhammad
Over the years of digital disruption, companies are heavily invested in social media to promote their brand and establish relationships centered around the brand, PT Nutrifood Indonesia in 2024 are shifting strategic focus on how to leverage the growing influence of employees in social media. This research combines conventional employee-based brand equity (EBE) scales with Instagram public data to examine the connection between EBE and employees' social media activity. The study aims to navigate employee’s role as influencer in PT Nutrifood Indonesia by assessing brand consistent behavior (BCB), brand endorsement (BE), and brand allegiance (BA) through questionnaires and social media qualitative scoring. The quantitative results are analyzed using PLS-SEM through SmartPLS4 software, consisting of reflective and formative model. The reflective model shows that all variables of EBE measurement have a strong reliability, internal consistency, discriminant validity and convergent validity. The formative model results show a linear positive relationship between exogenous & endogenous variables. The qualitative analysis of 570 Instagram contents revealed that the highest score is in BCB, image content (53%, n=303) and the lowest score is in BA, link branding (2%, n=13). Overall, Nutrifood employees have a high baseline of consistent brand behavior on social media, but lower scores on endorsement and allegiance indicate they have not quite explicitly endorsed the company or brands in their activities or profile. Integration of quantitative & qualitative data are processed through mixed-method sequential explanatory model using methodological triangulation which found that EBE has shown a high level of correlation with social media activities (R2 = 0.8341) and work experience (R2 = 0.8807). Employees who demonstrate a high EBE could potentially become employee influencers. This is because EBE aligns with the brand's values, for employee to establish authority and authenticity. The EBE integrative matrix is proposed to visualize the business solution, comparing qualitative and quantitative EBE scores. Employees who score high on both EBE scores are strong employee influencers, while those who score lower need a development related to highy significant exogenous factor (P value < 0,005), role clarity and brand commitment. This matrix can help employers to identify, monitor, control, and evaluate the extent to which employees' actions align with the brand. Therefore, companies should regularly identify and nurture potential employee influencers among their employees, because frontline employees' empowerment can lead to increased consumer trust, loyalty, and sales success. This research presents a novel measure of EBE that can be used and adopted for other companies in the future to navigate and leverage their employee roles as influencer in social media.